Pendidikan Keluarga dan Pola Komunikasi Serta Pengaruhnya Terhadap Pencegahan Kenakalan Siswa SMA Negeri 3 Lubuklinggau - Jun Purwadi (UIN Fatmawati Sukarno Bengkulu, 2022)
The problem in this research is whether there is an influence of Islamic religious education in the family and communication patterns to prevent the tendency of delinquency of students in SMA Negeri 3 Lubuklinggau. The purpose of this study was to reveal the influence of Islamic religious education in the family and communication patterns to prevent delinquency tendencies of students in SMA Negeri 3 Lubuklinggau. This type of research is field research with a quantitative approach. Quantitative research is a research approach that is often required to use numbers, starting from data collection, interpretation of the data and the appearance of the results. The population and sample in this study were 27 students of class XI of Social Sciences at Lubuk Lingga State Senior High School 3. Multiple linear regression test, is a linear relationship between two or more independent variables (X1, X2 X3) and the dependent variable (Y). The conclusion in this study is that there is a significant influence between Islamic religious education in the family and communication patterns on preventing delinquency of students in SMA Negeri 3 Lubuklinggau. This can be seen from the results of the simultaneous test (F test), where the determination coefficient value (R square) is 0.004, this explains that the effect of Islamic religious education in families and communication patterns on preventing delinquency of students at 3 Lubuk State Senior High School. Linggau is 0.04% while the remaining 99.96% is influenced by other variables besides the Islamic religious education variable in the family and good communication patterns.